Social Deconstruction of Digital Literacy in the Information Technology Era among Urban Families in Mataram City - Utomo, Jepri; Jayadi, Karta; Irwansyah Idrus, Idham; Torro, Supriadi; Najamuddin, Najamuddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The rapid expansion of digital technology has transformed social relations and reshaped family roles, particularly in digitally integrated urban societies. This study examines digital literacy not merely as a technical competence but as a social arena that deconstructs and reconstructs meanings, power relations, and educational functions within urban families. It focuses on the social conditions driving the widespread adoption of digital literacy among families in Mataram City. Using a qualitative approach within a constructivist-interpretive paradigm, data were collected through in-depth interviews, participant observation, and institutional triangulation. Analysis draws on social construction theory, symbolic interactionism, structuration theory, network society, and social deconstruction. The findings show that digital literacy is socially constructed through urban lifestyles, educational digitalization, and the normalization of digital devices in domestic spaces. Digital practices transform parental supervision, emotional interaction, and educational authority by redefining control, communication, and knowledge production. However, some families reconstruct these roles through dialogue, ethical regulation, and negotiated relationships between parental agency and technology. The study highlights critical family-based digital literacy as a strategic foundation for sustaining social cohesion and educational functions in digitally mediated urban societies